Psychosocial factors associated with talent development in UK female youth football players - Gledhill, A. (Loughborough University, 2016)
Psychosocial factors are the interrelated psychological, social and/or behavioural considerations that can influence talent development in football (Holt & Dunn, 2004). Despite this, the significant growth of female football worldwide, and the psychosocial challenges faced by female athletes during adolescence, scant scholarly attention has been afforded to the role of psychosocial factors in the development of talented female football players. Therefore the main aim of this thesis was to understand psychosocial factors associated with talent development in UK female football players. Study one systematically reviewed the literature on psychosocial factors associated with talent development in soccer. Following an extensive literature searching, selecting and appraisal process, three overarching themes of psychological, social and behavioural factors associated with talent development in soccer - underpinned by a total of 33 subthemes were created. The appraised literature has a moderate-to-high risk of reporting bias; had a significant bias towards adolescent, Caucasian, male, able-bodied, and European soccer players; and extant literature has demonstrated bias towards quantitative approaches and retrospective data collection methods. Consequently, study two began to address these reported biases by longitudinally and prospectively investigating the developmental experiences of English elite female youth soccer players. Through interviews, fieldwork and the use of composite sequence analysis, study two forwarded the importance of psychosocial considerations including the interaction between players and key social agents (soccer fathers, soccer brothers, soccer peers and non- soccer peers), elements of self-regulation and volitional behaviours, and the subsequent developmental benefits for their soccer careers. However, this study did not address the experiences of those who were unsuccessful in their attempts to achieve an elite female soccer career, nor did it collect primary data from other key social agents. Building on the critique of study two, study three sought to adopt an underutilised approach of negative case analysis by examining the experiences of players who had been unsuccessful in their attempts to forge a career in female soccer. Based on interviews former female players, their best friends, coaches and teachers, a grounded theory of talent and career development in UK female youth soccer players was produced. The theory posited that interactions with multiple social agents can affect the quality of talent development and learning environment that a player experiences, which can lead to adaptive player level benefits and changes (e.g., basic psychological need satisfaction; development of pertinent intra-individual constructs; optimal match preparation and training behaviours) and create a greater chance of career success. Study three also forwarded important culturally significant considerations for practitioners working with UK female soccer players, such as an understanding of dual career demands and the impact of role strain on female players. However, study three did not test any of the theoretical predictions offered by the grounded theory. Owing to the need to test predictions of grounded theories to assess their predictive validity, study four sought to test key predictions using a representative sample of English talented and elite adolescent female soccer players (N=137). As a result of the limited structural stability of the Basic Needs Satisfaction in Sport Scale and the Talent Development Environment Questionnaire (as demonstrated by significant cross loading of items, high bivariate correlations between subscales, and one example of an inadequate Cronbach s alpha), data was parcelled and the revised path hypothesis: perceptions of talent development environment > basic psychological needs satisfaction > career aspirations and beliefs > career intentions was produced. Path analysis supported the hypothesis. Supporting findings of studies two and three, regression analysis demonstrated that playing level positively predicted career beliefs, aspirations and intentions; whereas age negatively predicted these variables. Finally, TDEQ results indicated a perception that UK female soccer players that they can be written off before having the opportunity to fulfil their potential. Overall, this thesis has provided original and unique contributions to the sport psychology literature by enlightening the body of research to the developmental experiences of English female youth soccer players. It provides a developmental understanding scarcely evident in existing talent development literature. The interactional roles of multiple social agents have been elucidated and linked to psychosocial development, behavioural outcomes and talent and career progression within talented female players. The thesis has extended previous approaches to talent development in soccer by testing the predictions of the grounded theory. Initial evidence suggests that the proffered grounded theory is robust; however further research utilising structurally sound and ecologically valid measures would serve to further validate these claims.